MINERALIZATION STUDY OF RENAL RATS FOLLOWING OVARYOHYSTERECTOMY AND ADMINISTRATION HIGH DOSE CALCIUM CARBONATE - Misaco Yuniarti, Wiwik; Sari Yudaniayanti, Ira; Triakoso, Nusdianto (Jurnal Veteriner; Vol 9 No 2 (2008))
The aim of this study was to determine the effect of high dose calcium carbonate in rat (Rattus norvegicus) following ovaryohysterectomy. A total of twenty female rats at 13 week-old were used in this study. Following ovaryohitectomy, the animals were randomized in four treatment groups. Group P0 were :fed with standard food only P1, P2 and P2 groups treated with standard food but supplemented calcium carbonate respectively at the dose of 75 mg per animal per day, 225 mg per animal per day , and 450 mg per animal per day. The calcium carbonate supplement were given daily in the morning for 42 days. The experimental animals were sacrificed at 21 week-old. Calcium and phosphor level in sinister kidneys were determined by spectrofotometric method. The data obtained from this study were analysed using one way analysis of variance. No significant difference was observed in calcium level among four treatment groups, with the lowest level were found in P3 group. However, the phosphor level of P1 was significantly lower than those of P2 and P3 groups. The highest phosphor level was observed in P3 group, indicating a phosphorous retension and the signs of renal failure.
Keywords: ovaryohysterectomy, menopause, estrogen, calcium carbonate, calcium, phosphor